THEORETICAL STUDY OF THE BENDING OF THE COLASNIC IN THE PROCESS OF INSTALLING THE REPLACEMENT ELEMENT TO THE COLASNIC - Botirov , A.A. (Educational Research in Universal Sciences, 2023)
A theoretical calculation of a new construction of a rectangular colossal structure with minimal flexural and deformable properties for a sawing machine. The rational design of the exchangeable element to be installed on the working part of the columnar in the new construction and the bending of the columnar when installing the exchangeable element on the columnar. Кўп ишлатиладиган, ресурс тежамкор колосник билан жиҳозланган аррали жиннинг энергетик ва физик- механик кўрсаткичлари аниқлаш учун боғланишлар ишлаб чиқиш.